2020
DOI: 10.1001/jamaophthalmol.2020.3820
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Low-Dose Atropine Eyedrops for the Treatment of Myopia Progression in Chinese Children

Abstract: IMPORTANCEBecause studies have suggested that atropine might slow the progression of myopia in children, randomized clinical trials are warranted to understand this potential causal relationship.OBJECTIVE To evaluate the efficacy and safety of atropine, 0.01%, eyedrops on slowing myopia progression and axial elongation in Chinese children. DESIGN, SETTING, AND PARTICIPANTSThis was a randomized, placebo-controlled, double-masked study. A total of 220 children aged 6 to 12 years with myopia of −1.00 D to −6.00 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
122
3
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(157 citation statements)
references
References 43 publications
15
122
3
3
Order By: Relevance
“…It is well established that there is slowing of physiological change in AL in older children 19 We also found that the children with 0.01% atropine had a more rapid AL elongation and a worse myopic control effect than 0.02% atropine 13 . Other reports have also found a concentration-dependent response in myopia control with low concentration atropine 6,10,12,14 . Side effects and adverse effects are reportedly similar in 0.01% and 0.02% atropine 13,20 , suggesting that if children using 0.01% atropine are not achieving adequate myopia control, changing to the 0.02% concentration could be considered.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…It is well established that there is slowing of physiological change in AL in older children 19 We also found that the children with 0.01% atropine had a more rapid AL elongation and a worse myopic control effect than 0.02% atropine 13 . Other reports have also found a concentration-dependent response in myopia control with low concentration atropine 6,10,12,14 . Side effects and adverse effects are reportedly similar in 0.01% and 0.02% atropine 13,20 , suggesting that if children using 0.01% atropine are not achieving adequate myopia control, changing to the 0.02% concentration could be considered.…”
Section: Discussionmentioning
confidence: 81%
“…In a one year study of Korean myopic children 10 , the AL elongation was about 0.44 ± 0.32mm, 0.30 ± 0.24mm and 0.23 ± 0.25mm in 0.01%, 0.025% and 0.05% atropine, respectively. In a study of Chinese myopic children 14 , the AL elongation after one year was about 0.32 ± 0.19mm and 0.41 ± 0.09mm in 0.01% atropine and placebo, respectively. By comparison, in the present study the AL elongation was 0.36 ± 0.19mm with 0.01% and 0.30 ± 0.22mm with 0.02% atropine, 0.02% atropine had a better effect on myopia control than 0.01% atropine 13 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations